2015
DOI: 10.1371/journal.pone.0070239
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Irrational Parenthood Cognitions in an Iranian Group of Infertile Women

Abstract: ObjectivesThe aim of this study was to investigate possible predictors of irrational parenthood cognitions among infertile women seeking treatment.MethodsIn a cross-sectional study, 300 women who visited an Infertility Center in Iran during 2010 were studied. A pre-validated inventory was used to assess irrational parenthood cognitions. Potential predictors of the total irrational parenthood cognitions score were assessed.ResultsMean irrational parenthood cognition score was 39.7(Range 0–56). Through bivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…The IPC score ranged between 0 and 56, with higher scores denoting a higher IPC and more need for having a child and having a happier life . These results are consistent with those studies conducted in Iran, which obtained a score of 38 to about 40 . Fekkes et al.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The IPC score ranged between 0 and 56, with higher scores denoting a higher IPC and more need for having a child and having a happier life . These results are consistent with those studies conducted in Iran, which obtained a score of 38 to about 40 . Fekkes et al.…”
Section: Discussionsupporting
confidence: 87%
“…8 These results are consistent with those studies conducted in Iran, which obtained a score of 38 to about 40. 10,18 Fekkes et al in the Netherlands reported the highest score of IPC to be 34.1 in young infertile women. 8 The higher value of IPC in Iran compared to other studies can be explained by the existing cultural, social, and ethnic differences in the goal of marriage and childbearing in eastern communities compared to that in western communities.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional survey of 300 women from an Iranian infertility clinic by Laya Farzadi [ 19 ] revealed that the mean irrational parenthood cognition score was 39.7, which is similar to the results of this study, indicating that the surveyed patients with RIF had an internal desire to have a child to live a happy life. The outcomes of the cross-sectional study are comparable to those of the current study.…”
Section: Discussionsupporting
confidence: 84%
“…This was similar to the mean ages of 32.96 years reported by Rahebi et al [10], 31.77 years by Ozturk et at. [11], 31.6 years by Fatma et al [12], 31.66 years by Fatemeh et al [13] and 31.1 years by Farzadi et al [14]. Other studies reported lower mean ages of infertile respondents of 29.54 years, 30.50 years, 26.88 years and 28.27 years respectively [8,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%